2008
DOI: 10.1128/aem.01303-08
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Kingdom Amplification Using Bacteria -Specific Primers: Complications for Studies of Coral Microbial Ecology

Abstract: PCR amplification of pure bacterial DNA is vital to the study of bacterial interactions with corals. Commonly used Bacteria-specific primers 8F and 27F paired with the universal primer 1492R amplify both eukaryotic and prokaryotic rRNA genes. An alternative primer set, 63F/1542R, is suggested to resolve this problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
123
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(133 citation statements)
references
References 33 publications
1
123
1
Order By: Relevance
“…Although there was no detection of ampicillin-resistant isolates from food animals in the current study, there has been a report of CC17 in food animal samples elsewhere. 8 Thus, screening of ampicillin-resistant enterococci and major humanadapted strains, such as CC17, continues to remain important in Korea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there was no detection of ampicillin-resistant isolates from food animals in the current study, there has been a report of CC17 in food animal samples elsewhere. 8 Thus, screening of ampicillin-resistant enterococci and major humanadapted strains, such as CC17, continues to remain important in Korea.…”
Section: Discussionmentioning
confidence: 99%
“…All isolates were confirmed as enterococci by polymerase chain reaction (PCR) and identified as E. faecalis or E. faecium by species-specific PCR or other enterococcal species by 16S ribosomal RNA sequencing. 8,13,17 The primers used in the current study are shown in Table 1. 1,4,8,11,13,17,25,30,37 Antimicrobial susceptibility tests Antimicrobial susceptibility tests were performed for 6 antibiotics (vancomycin, erythromycin, tetracycline, chloramphenicol, ampicillin, and ciprofloxacin) by the disk diffusion method.…”
Section: Bacterial Isolation and Identificationmentioning
confidence: 99%
“…The variable regions V1-V9, of the 16S rRNA genes (rDNAs) have been used for species identification (Lane, 1991;Weisburg et al, 1991), but also to assess bacterial Neg DN VFR1 ID3 ID2 ID1 ID1 ID2 H3 H2 H1 H3 H2 H1 H3 H2 diversity in several habitats for the past 17 years. However, the use of the universal primer single mismatch 27F has recently been criticised for the its amplification efficiency (Frank et al, 2008;Galkiewicz and Kellogg, 2008), and a new 27F priming-binding site has been suggested that can accommodate mismatching allowing minimal loss of efficiently and without compromising specificity with the reduction of annealing temperature. D. nodosus was also not detected in the 61 709 sequences produced by pyrosequencing; however, analysis of the sequence reads removed during quality control checks revealed that D. nodosus sequences were amplified but removed due to sequence errors or mis-priming when using bacterial universal primers (see material and methods).…”
Section: Profiling Bacterial Community By Dggementioning
confidence: 99%
“…Bacterial DNA was extracted using the protocol described by Mahuku (2004) with the following modifications: bacterial cells were obtained by growing them in NB medium at 28 °C for 48 h. After suspending the precipitate in 100 µL of 1X TE, 2 µL of RNAsa were added (1 mg mL -1 ) and then incubated in a water bath at 37 °C for 1 h. The DNA quality was verified by electrophoresis in agarose gel. Bacteria were identified by partially amplifying the 16S rADN gene using universal primers 27F (5´AGAGTTTGATCMTGGCTCAG-3´) and 1492R (5´TACGGHTACCTTGTTACGACTT-3´) under the PCR conditions described by Galkiewicz and Kellogg (2008). DNA amplification and sequencing were carried out using Macrogen (DNA Sequency Service.…”
Section: Aislamiento De Bacterias Endófitas De Raícesmentioning
confidence: 99%